The Effect of Topical Cefepime Solution on Outer Hair Cell Function of Rats - Apuhan, Tayfun; Yildirim, Yavuz Selim; Aksoy, Fadlullah; Balikci, Hasan Huseyin; Kaya, Mehmet Onur (Aves, 2011)
Objectives: The current study was designed to investigate the ototoxic effect of topical cefepime solution on the outer cell function of cochlea by measuring distortion product otoacoustic emission (DPOAE) amplitudes. Study Design: Prospective controlled animal study. Materials and methods: A 50 mg/ml cefepime solution was injected into the left middle ear space of 8 of the rats with dental needle via transtympanic route 2 times per day for 7 days (Group la), and a 1 ml %0.9 NaCl solution was injected to the right ear of the same rats 2 times per day for 7 days (Group 1b). An 80 mg/ml gentamycine solution was injected to the left middle ear space of 4 of the 12 rats of the same way (Group2a), and a 1 ml %0.9 NaCl solution was injected into the right ear of the same rats (Group 2b). DPOAE measurements were then obtained for both experimental and control ears before day 0 (baseline) and days 3, 7, and 28 after the initiation of treatment. Results: DPOEA measurements on day 0 were not significantly different between Groups 1a and 2a. DPOAE measurements during 0-28 days were not significantly different between Group 1a and Group 1b. Among groups 2a and 2b, DPOEA measurements on day 28 were significantly lower within all frequencies compared to day 0. Overall, DPOAE measurements decreased only with gentamycine (p<0,05). Conclusions: The present study demonstrates that a topical cefepime solution does not affect DPOAE amplitudes after application to the middle ear cavity of rats.
Keywords: Ototopical Drops; Ototoxicity; Gentamicin; Ciprofloxacin